Strategi Pemasaran dalam Upaya Meningkatkan Jumlah Anggota pada Koperasi Simpan Pinjam dan Pembiayaan Syariah Mitra Usaha Ideal (KSPPS MUI) Cabang Ketanen Kabupaten Gresik - Fatimatu Zahroh; Siswadi Siswadi (Al-Muzdahir : Jurnal Ekonomi Syariah, 2022)
The term marketing strategy is not just promotion, but is how to satisfy customers with services provided so that customers are comfortable with cooperatives. This study explains the marketing strategy in an effort to increase the number of members at KSPPS MUI Ketanen Branch, Gresik Regency, which has a background of 2 KSPPS MUI branch offices in Panceng sub-district, which is a differentiator from other sub-district branch offices. This research is a qualitative descriptive field research, the subject of this research is the head of the KSPPS MUI Ketanen branch, as well as several informants, namely marketing employees of the KSPPS MUI Ketanen branch and several members of the KSPPS MUI Ketanen branch. Data collection techniques are carried out by observation, interviews and documentation. The data validation technique is carried out using source triangulation by collecting similar data and information from a variety of different sources. The results of the analysis of the marketing strategy in an effort to increase the number of members in the Ideal Business Partners Savings and Loans and Sharia Financing cooperative (KSPPS MUI) Ketanenen Branch concluded that the obstacles in increasing the number of members at the KSPPS MUI Ketanen branch included the schedule of market grebek which coincided with working hours making the grebek program the market is less than optimal, the nature of various members and payments outside working hours. The supporting factors in increasing the number of members include friendly service, being able to do transactions at home without having to come to the office and strategic places.